Enhanced Structural, Optical, and Electronic Properties of In2O3 and Cr2O3 Nanoparticles Doped Polymer Blend for Flexible Electronics and Potential Applications - Hashim, Ahmed (Journal of inorganic and organometallic polymers and materials, 2020)
This paper aims to investigate the structural, optical, electronic and electrical properties of PVA/PVP blend and PVA/PVP blend doped with In 2 O 3 and Cr 2 O 3 nanoparticles to use it for various flexible electronics devices like solar cell, sensors diodes, electronics gates, transistors have low cost, high corrosion resistance, low energy gap, flexible, low weight, high optical and electrical conductivities. The results indicated that absorbance of PVA/PVP blend improved about 30% and 34 with the increase of In 2 O 3 and Cr 2 O 3 nanoparticles concentrations. The energy gap value of PVA/PVP blend was reduces from 2.8 eV of PVA/PVP to 1.2 eV and 1.77 eV as In 2 O 3 and Cr 2 O 3 nanoparticles concentrations increase. Doping PVA/PVP with In 2 O 3 and Cr 2 O 3 nanoparticles enhance the optical constants, electronics parameters and electrical conductivity. The obtained results showed that the doping PVA/PVP blend with In 2 O 3 and Cr 2 O 3 improved the structural, optical, electronic and electrical characteristics which make the (PVA/PVP/In 2 O 3 ) and (PVA/PVP/Cr 2 O 3 ) nanocomposites are promising materials for flexible optoelectronics fields in the development of electronics applications.